2021
DOI: 10.3390/nu13113801
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Pancreatic Cancer Treatment: From Traditional Medicine to Modern Drug Discovery

Abstract: Pancreatic cancer, the seventh most lethal cancer around the world, is considered complicated cancer due to poor prognosis and difficulty in treatment. Despite all the conventional treatments, including surgical therapy and chemotherapy, the mortality rate is still high. Therefore, the possibility of using natural products for pancreatic cancer is increasing. In this study, 68 natural products that have anti-pancreatic cancer effects reported within five years were reviewed. The mechanisms of anti-cancer effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…One promising approach is to use knowledge from traditional Eastern medicine. Many substances used in traditional Eastern medicine have been studied for decades, and multiple studies have investigated their effects on cancer [ 16 , 17 , 18 , 19 , 20 ]. Furthermore, traditional Eastern medicine has a distinctive classification method for the effects of therapeutic substances.…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
See 1 more Smart Citation
“…One promising approach is to use knowledge from traditional Eastern medicine. Many substances used in traditional Eastern medicine have been studied for decades, and multiple studies have investigated their effects on cancer [ 16 , 17 , 18 , 19 , 20 ]. Furthermore, traditional Eastern medicine has a distinctive classification method for the effects of therapeutic substances.…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…An adequate combination of treatment methods that act on multiple targets or work synergistically would help develop new treatment options for CIPN. In addition, the effects of many substances on cancer have been studied extensively in recent decades [ 16 , 17 , 18 , 19 , 20 ]. Considering that the treatment for CIPN should not deteriorate cancer, these pre-established results are advantageous for selecting the traditional Eastern medicine approach as a treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the accumulation of ROS decreases mitochondrial membrane potential (MMP) and mitochondria depolarization. The presence of ROS leads to cell cycle arrest at the G2/M phase, followed by the accumulation of DNA damage and induction of apoptosis [ 102 , 103 ]. Other researchers reported that marine extracts from nudibranchs, brown algae, and Arctic fungi trigger the intracellular accumulation of ROS in cancer cells originated from human CRC and PC, leading to apoptosis [ 36 , 58 , 61 ].…”
Section: Mechanisms Of Action Of Mnps In Crc and Pcmentioning
confidence: 99%
“…Herbal medicines can potentiate the activity and diminish the adverse effects and organ toxicities of chemotherapy. Moreover, medicinal plants themselves and natural product-derived compounds can target cancer cells effectively and selectively, without affecting normal cells [ 1 , 15 ]. This might be correlated to their diverse chemotypes and pharmacological effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%